Health of Elderly Mexican American Adults and Family Caregiver Distress. (April 2015) - Rote, Sunshine; Angel, Jacqueline L.; Markides, Kyriakos
Using newly available data on family caregivers from a large epidemiological study of elderly Mexican-origin adults (Hispanic Established Population for the Epidemiologic Study of the Elderly [HEPESE], 2010/2011), we identify which types of impairment (functional, psychological, and cognitive) in the elderly individual are associated with family caregiver depressive symptoms. Results from ordinary least squares regressions using 626 caregiver–care recipient dyads demonstrate that more severe mobility limitations (Performance-Oriented Mobility Assessment), social disability (instrumental activities of daily living), neuropsychiatric disturbances related to cognitive decline (Neuropsychiatric Inventory), and depressive symptoms in the elderly subject are positively associated with caregiver psychological distress. Perceived social stress partially accounts for these associations. We also identify certain segments of this caregiver population that are especially vulnerable to burden when caring for a family member with high levels of impairment, namely female and low-income caregivers. These vulnerabilities should be the focus of intervention efforts to reduce stress and improve the emotional and psychological well-being of Mexican-origin caregivers.